Cadre Knowledge And Self-Efficacy Following Care For Child Development Post Intervention: A Four-Year Prospective Follow-Up Study - Tri Kurniasih, Amara; Widyawati, Widyawati; Akhmadi, Akhmadi; Haryanti, Fitri (Poltekkes Kemenkes Surakarta, 2023)
Background: Stunting is a significant malnutrition problem in Indonesia, and community health cadres play a vital role in addressing it through programs like Care for Child Development (CCD) training. This study aimed to delineate the knowledge and self-efficacy of cadres who participated in CCD training in Yogyakarta in 2018, comparing their status in 2022. Methods: In October 2022, a quantitative cross-sectional approach was utilized to examine the knowledge and self-efficacy of 56 cadres who had undergone CCD training in 2018, organized by the same authors and documented in a prior publication, with participants selected through total sampling. Three instruments were utilized, including a participant demographic survey, the CKCDI, and the GSES. The paired t-test was employed to analyzed the data. Results: The study's results reveal a significant difference (p=0.002) in the mean knowledge scores of cadres following their participation in the Care For Child Development (CCD) training program in 2018 and four years later. The mean score was 13.39 in 2018, decreased to 11.9 in 2022. Likewise, the self-efficacy component among cadres exhibited a reduction, with mean scores of 30.93 in 2018 and 29.4 in 2022. However, it is important to note that there is no statistically significant difference in self-efficacy (p=0.106). The decline in average knowledge scores over the four-year period may be attributed to potential knowledge decay. Conclusion: This study underscores the significance of sustained training and support for community health workers, emphasizing the need for flexible approaches to maintain their knowledge and self-efficacy over time.